Strengthening MSME Managerial Capacity to Support Sustainable Development Goals (SDGs): A Study of the Local Culinary Sector - Dian Senly Andika; Rizma Fauziyah; Agung Winarno; Agus Hermawan (TIN: Terapan Informatika Nusantara, 2026)
Micro, Small, and Medium Enterprises (MSMEs) frequently encounter managerial limitations that hinder business sustainability and reduce their potential contribution to the Sustainable Development Goals (SDGs). This study aims to analyze how managerial strengthening through a mentoring program enhances MSME capacity building and supports SDG achievement. The research was conducted at Dimsum Bolobox, a culinary MSME located in Surabaya, Indonesia, using a qualitative case study approach involving one business owner as the primary participant and mentoring activities carried out over approximately fifteen weeks (February–May 2026). Data were collected through observation, interviews, documentation, and participatory mentoring, and analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that managerial strengthening resulted in significant improvements across four managerial dimensions: marketing, operational management, financial management, and business legality. The MSME successfully implemented a structured content calendar, insight-based digital marketing evaluation, standard operating procedures (SOPs), production recording systems, attendance monitoring, simple financial bookkeeping, comprehensive cost of goods sold (COGS) calculations, and obtained a Business Identification Number (NIB). These interventions transformed previously informal business practices into more systematic managerial processes and strengthened the owner’s confidence and decision-making capacity. The study further demonstrates that managerial strengthening functions as a multidimensional capacity-building process that simultaneously develops technical, organizational, and psychological capabilities while creating potential contributions to SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 12 (Responsible Consumption and Production). These findings provide empirical evidence that practice-based mentoring can serve as an effective strategy for improving MSME sustainability and supporting long-term sustainable development.